Profil Antropometrik dan Kondisi Fisik Atlet Futsal Muda Ditinjau dari Perspektif Fisiologi Olahraga - Alviana, Irana Mery; Gemael, Qorry Armen; Limastyningrum, Rafa Dinnantra; Lutfanpadil, Muhammad; Marhandika, Irfan; Rifky Arifin, Muhammad; Almuhtadi, Ajri Nurli (Institut Teknologi Bandung, 2026)
This study aims to analyze the anthropometric profile and physical condition of adolescent futsal athletes and relate them to aspects of sports physiology. The method used is descriptive quantitative with 10 futsal athletes aged 14–16 years as research subjects. The instruments used include anthropometric measurements (weight, height, and body mass index/BMI), speed (20-meter sprint), power (vertical jump), strength (wall sit, push-up, sit-up), and cardiorespiratory endurance (12-minute Cooper test). Data analysis was carried out using descriptive statistics in the form of minimum, maximum, average, and standard deviation values. The results showed that the average BMI of athletes was 18.94 kg/m² in the normal category. The speed component had an average of 3.32 seconds (moderate category), power was 42.20 cm (moderate category), muscle strength showed varying results with moderate to good categories, and cardiorespiratory endurance was 2216 meters (moderate category). Physiologically, these results indicate that futsal athlete performance is influenced by the interaction of the anaerobic, aerobic, and neuromuscular energy systems. The study concluded that the athletes' general physical condition was moderate to good, but improvements in aerobic endurance and muscle power were still needed. Therefore, it is recommended to implement exercise physiology-based training programs such as high-intensity interval training (HIIT) and plyometric training to optimally improve the performance of adolescent futsal athletes.